THE IMPACT OF HEDGING CONTRACTS IN FIRM VALUE - Myrta, Shirli; Zárybnická Žárová, Marcela, 1959-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
The main aim of this paper is to provide evidence if the hedging technique impacts the firm values in a positive or negative way, does not impact at all or it only has a slightly low impact. The hypothesis will be the impact of hedging techniques in firms value. Firstly in the study there will be explained the literature review part where will be given what hedging is and the description in details of the different hedging technique used. The most common types of techniques are financial derivatives like contracts, swaps, options etc.. There is done a SWOT analysis of hedging techniques to try to understand better what strength, opportunities, weaknesses and threatens arises from it. It is followed from the part where there are explained the positive and negative impacts of hedging or the advantages and disadvantages. Moreover, at the end of the literature review part it is explained how multinational companies through out the world deal with different risks and how they try to reduce it. The second part of the paper is composed of description of the variables and the test done. It explains the methodology used. The variables that are tested in the text are net sales, market capitalization, income tax expense, financial result and net profit. Based on the result of the study on Porsche case conducted on this paper we can see that the hedging contracts impact the firms in positive way, but the firm value is affected by many other variables as well. The more hedging the company does the more profits it has. The data used in the paper is secondary data.
Vedoucí práce: Marcela Zárybnická Žárová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses